Multiplex Lateral Flow Immunoassay: An Overview of Strategies towards High-throughput Point-of-Need Testing - Anfossi, Laura (Biosensors (Basel), 2018)
Simultaneous measurement of different substances from a single sample is an emerging issue for achieving efficient and high-throughput detection in several fields of application. Although immunoanalytical techniques have well-established and prevailing advantages over alternative screening analytical platforms, one of the incoming challenges for immunoassay is exact multiplexing. Lateral flow immunoassay (LFIA) is a leading immunoanalytical technique for onsite analysis, thanks to its simplicity, rapidity, and cost-effectiveness. Moreover, LFIA architecture is adaptable to multiplexing, and is therefore a possible answer to the pressing demand of multiplexing point-of-need analysis. This review presents an overview of diverse approaches for multiplex LFIA, with a special focus on strategies based on new types of magnetic, fluorescent, and colored labels.